2007
DOI: 10.3928/15428877-20070501-03
|View full text |Cite
|
Sign up to set email alerts
|

Adjustable Suture Surgery for Correction of Various Types of Strabismus

Abstract: <H4>BACKGROUND AND OBJECTIVE</H4> <P>This study was conducted to analyze the efficacy of the adjustable suture technique for correction of strabismus in patients with different types of strabismus.</P><H4>PATIENTS AND METHODS</H4> <P>This was an observational case series of patients who underwent the adjustable suture technique for correction of strabismus. A total of 33 adult patients (16 males and 17 females) with a minimum postoperative follow-up period of 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…We describe a modification of the existing techniques of adjustable-suture strabismus surgery, [2][3][4][5][6][9][10][11][12][13][14][15][16] which we call the short tag noose adjustable technique. Saunders and O'Neil 11 devised a technique in which postoperative knot tying was required only in patients who underwent adjustment.…”
Section: Commentmentioning
confidence: 99%
“…We describe a modification of the existing techniques of adjustable-suture strabismus surgery, [2][3][4][5][6][9][10][11][12][13][14][15][16] which we call the short tag noose adjustable technique. Saunders and O'Neil 11 devised a technique in which postoperative knot tying was required only in patients who underwent adjustment.…”
Section: Commentmentioning
confidence: 99%
“…Since the popularization of the adjustment surgery in the 1970s [ 2 , 10 ], many studies have addressed adjustment and focused on introducing different adjustment techniques [ 3 , 11 , 12 ] or demonstrating the effectiveness of the adjustment technique itself by comparing surgical results between adjustment and no adjustment groups [ 13 , 14 ]. In addition, some studies focused specifically on conditions such as adjustment to thyroid-associated strabismus [ 15 ] or all types of strabismus including exotropia, esotropia, and vertical strabismus [ 9 , 16 ]. As strabismus surgery for exotropia, lateral rectus recession or medial rectus resection can be performed.…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable literature addressing resected muscle adjustment [ 8 , 9 , 12 ]. Hong et al [ 8 ] reported that they resected the rectus muscle and adjusted it in patients with sensory exotropia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations